EFFECT OF PLANT DENSITY ON OIL YIELD OF CASTOR (RICINUS COMMUNIS L) IN APPLICATION OF NITROGEN LEVELS CONDITIONS - Farahani, H. A.; Aref, B. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
This experiment was conducted at Qazvin, Iran in 2005. Field experiment was carried out by a split plot design with 4 replications. The factors which studied were nitrogen levels 0, 40, 80 and 120 kg ha-1 and plant density with 2.5, 4 and 5.5 plant m-2. The results showed that nitrogen application significant effect on seed yield, oil yield and biological yield (α=1%), seed thousand weight and oil percent (α=5%). Means comparison showed that highest seed yield, biological yield and oil yield were achieved under application of 80 kg ha-1 nitrogen application, highest seed thousand weight was achieved under 120 kg ha-1 nitrogen application and highest oil percent was achieved under 40 kg ha-1 nitrogen application. Also plant density significant effect on seed yield, oil yield and biological yield (α=1%), seed thousand weight and oil percent (α=5%). Means comparison showed that highest seed yield, biological yield and oil yield were achieved under 5.5 plant m-2, highest seed thousand was achieved weight under 4 plant m-2 and highest oil percent was achieved under 2.5 plant m-2. Interaction of nitrogen application and plant density significant effects on oil yield and oil percent (α=1%), seed yield, seed thousand weight and biological yield (α=5%). The results of this experiment showed that oil percent decreased under increase of nitrogen application and plant density but oil yield increased in conditions that this can have very important for achieve to maximum oil yield of castor. Key words: Castor, nitrogen, plant density and oil yield